2017
DOI: 10.1097/mpg.0000000000001525
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related Quality of Life in Pediatric Patients With Chronic Hepatitis B Living in the United States and Canada

Abstract: Objectives To determine if selected socio-demographic and HBV-specific clinical factors are associated with health-related quality of life (HRQoL) among pediatric patients chronically infected with hepatitis B virus (HBV). Methods Children with chronic HBV enrolled in the Hepatitis B Research Network completed the Child Health Questionnaire (CHQ) at study entry. Caregivers of children 5–<10 years completed the parent-reported PF50; youth 10–< 18 years completed the child-reported CF87. We examined univariabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
2
4
1
1
Order By: Relevance
“…We found that HRQOL was impaired in CHC children in comparison with healthy persons, where, scores of physical and psychosocial domains of CHQ (Child and Parent forms) were significantly reduced in those patients than controls. These results were in agreement with Nydegger et al, 16 and Schwarzenberg et al, 17 who used the CHQ for measuring HRQOL of the study children. Results of the current study were consistent with previous studies that reported a significant reduction in HRQOL of these patients as compared with population controls.…”
Section: Discussionsupporting
confidence: 92%
“…We found that HRQOL was impaired in CHC children in comparison with healthy persons, where, scores of physical and psychosocial domains of CHQ (Child and Parent forms) were significantly reduced in those patients than controls. These results were in agreement with Nydegger et al, 16 and Schwarzenberg et al, 17 who used the CHQ for measuring HRQOL of the study children. Results of the current study were consistent with previous studies that reported a significant reduction in HRQOL of these patients as compared with population controls.…”
Section: Discussionsupporting
confidence: 92%
“…This study of 174 participants followed across 5 years represents the largest and longest examination of HRQoL in youth with CHB. As we previously reported, baseline HRQoL in our North American cohort of youth with CHB was good overall, although a higher liver disease symptom count was associated with lower (ie, worse) Bodily Pain, Behavior, Mental Health, and Self-esteem subscale scores (2). In this report of longitudinal data among the same cohort, we show remarkable stability over 5 years across the majority of HRQoL subscales.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, the relatively higher variability in responses over time may be a function of having assessed a greater number of factors. Although the number of liver disease symptoms was associated with baseline Behavior, Mental Health, and Self-esteem subscale scores in this cohort (2), neither the number of liver disease symptoms at baseline, nor change in the number of liver disease symptoms from baseline, predicted or correlated with changes in these HRQoL subscales over time. In fact, very few predictors or correlates of change in HRQoL subscales were identified.…”
Section: Discussioncontrasting
confidence: 66%
“…The patient population consisted of patients with autoimmune or cholestatic liver disease (19 studies), [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] chronic hepatitis B or C (35 studies), [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] NAFLD or NASH (15 studies), [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , …”
Section: Resultsunclassified
“…[94] , [95] , [96] , [97] , [98] , [99] , [100] , [101] , [102] Six studies explored the quality of life in children with liver disease (3 in children with autoimmune or cholestatic liver disease, 9 , 12 , 23 2 in children with NAFLD, 70 , 71 and 1 in children with hepatitis B). 52 A total of 37,283 patients participated in the included studies. Half of the studies included patients aged 50 years or older.…”
Section: Resultsmentioning
confidence: 99%